Study on the behavior of monopiles used to founding offshore wind turbines - العبد الله صفوان (Latakia University Journal -Engineering Sciences Series, 2024)
Horizontally loaded piles used in founding electric power generation fans are affected by wind forces and repeated wave loads applied to them. This research is a computer modeling and analytical study of a loaded monopile pile which is used as a foundation for a offshore wind turbine fixed in a medium compacted and compacted sandy soil (sea bed). In this research is Hardening Soil model (HS) used for the soil surrounding the pile. The horizontal displacement values are determined due to several parameters. It is shown that the horizontal displacement of the monoopile is controlled by several parameters such as: its embedded length, its diameter, the height of the sea water, the value of the total horizontal force and its arm Calculations show that cyclic loading increases the horizontal displacement by 30%, and that the soil subgrade reaction coefficient distribution.with depth is not linear in sandy soil and Rees’ method for calculating horizontally loaded piles is not very suitable for monopile piles, especially in the displacement and moment distribution diagrams .